Variation of GP antibiotic prescribing tendency for contacts with out-of-hours primary care in Denmark - a cross-sectional register-based study - Linda Huibers; Claus Høstrup Vestergaard; Ellen Keizer; Bodil Hammer Bech; Flemming Bro; Morten Bondo Christensen (Taylor & Francis Group, 2022)
AbstractObjective To study variation in antibiotic prescribing rates among general practitioners (GP) in out-of-hours (OOH) primary care and to explore GP characteristics associated with these rates.Design Population-based observational registry study using routine data from the OOH primary care registration system on patient contacts and antibiotic prescriptions combined with national register data.Setting OOH primary care of the Central Denmark Region.Subjects All patient contacts in 2014-2017.Main outcome measures GPs' tendency to prescribe antibiotics. Excess variation (not attributable to chance).Results We included 794,220 clinic consultations (16.1% with antibiotics prescription), 281,141 home visits (11.6% antibiotics), and 1,583,919 telephone consultations (5.8% antibiotics). The excess variation in the tendency to prescribe antibiotics was 1.56 for clinic consultations, 1.64 for telephone consultations, and 1.58 for home visits. Some GP characteristics were significantly correlated with a higher tendency to prescribe antibiotics, including 'activity level' (i.e. number of patients seen in the past hour) for clinic and telephone consultations, 'familiarity with OOH care' (i.e. number of OOH shifts in the past 180 days), male sex, and younger age for home visits. Overall, GP characteristics explained little of the antibiotic prescribing variation seen among GPs (Pseudo r2: 0.008-0.025).Conclusion Some variation in the GPs' tendency to prescribe antibiotics was found for OOH primary care contacts. Available GP characteristics, such as GPs' activity level and familiarity with OOH care, explained only small parts of this variation. Future research should focus on identifying factors that can explain this variation, as this knowledge could be used for designing interventions.KEY POINTSCurrent awareness:Antibiotic prescribing rates seem to be higher in out-of-hours than in daytime primary care.Most important results:Antibiotic prescribing rates varied significantly among general practitioners after adjustment for contact- and patient-characteristics.This variation remained even after accounting for variation attributable to chance.General practitioners' activity level and familiarity with out-of-hours care were positively associated with their tendency to prescribe antibiotics.